2020
DOI: 10.1002/jum.15568
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of Real‐Time Shear Wave Elastography in Diagnosing the Depth of Infiltrating Muscular Layer of Endometrial Cancer

Abstract: Objective-To explore the clinical value of real-time shear wave ultrasonic elastography in diagnosing the depth of infiltrating muscularis of endometrial cancer.Methods-Seventy-one patients with stage I endometrial cancer infiltrating the myometrium and 37 patients with normal physical examination were enrolled and divided into three groups: endometrial cancer superficial muscle infiltration group, endometrial cancer deep muscle infiltration group, and normal control group. After completing 2-dimensional ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Similar results were obtained after adjusting for endometrial thickness, BMI, basal sex hormone levels, and antral follicle count. The women in Q1 (OR, 0.322; 95% CI, 0.135-0.768), Q2 (OR, 0.407; 95% CI, 0.196-0.843), and disordered arrangements can cause increased interstitial pressure and enhanced hardness [22]. When a blastocyst is implanted into the uterus, endometrial stromal cells undergo extensive proliferation, differentiation, vascular remodeling, and immune cell recruitment in a process known as decidualization, which is essential for a successful pregnancy [47].…”
Section: Associations Between Endometrial Elasticity and Clinical Pre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained after adjusting for endometrial thickness, BMI, basal sex hormone levels, and antral follicle count. The women in Q1 (OR, 0.322; 95% CI, 0.135-0.768), Q2 (OR, 0.407; 95% CI, 0.196-0.843), and disordered arrangements can cause increased interstitial pressure and enhanced hardness [22]. When a blastocyst is implanted into the uterus, endometrial stromal cells undergo extensive proliferation, differentiation, vascular remodeling, and immune cell recruitment in a process known as decidualization, which is essential for a successful pregnancy [47].…”
Section: Associations Between Endometrial Elasticity and Clinical Pre...mentioning
confidence: 99%
“…Elastic ultrasound has been continuously applied in gynecological clinic, which can distinguish the pathophysiological changes of the endometrium and is important in evaluating the physiological state changes of tissues. It performs well in the differential diagnosis of uterine diseases, such as endometrial hyperplasia, endometrial carcinoma, submucosal leiomyoma, and endometrial polys [21,22]. It is also helpful for determining the depth of the infiltrating myometrium in endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For an accurate measurement of tissue elastography, operator needs to have certain training and operation experience. 33 In the study of Zhao et al 15 the operator conducted 30 cases of training first to improve data repeatability. In our study SWE measurements were performed by an experienced radiologist with more than 5 years of experience in SWE studies.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Notably, there is anisotropy in the uterine myometrium, and we believe that the index Cs, rather than E, is more suitable to assess the stiffness ratio of the endometrium to the myometrium. Zhao et al reported that the determination of endometrial cancer by SWE can determine whether it has invaded the myometrium and the depth of myometrial invasion, which can clinically determine the surgical method and determine the prognosis [ 46 ]. Although there are limited studies, the accuracy of SWE in diagnosing endometrial disease is outstanding.…”
Section: Endometrial Tumorsmentioning
confidence: 99%
“…Fu et al studied SWE in CC ( n = 40), benign cervical lesions ( n = 40), and 40 healthy volunteers, and the results showed that the mean Cs of cervical cancer patients were significantly higher than benign cervical lesions and normal cervix ( p < 0.05). The results showed that SWE was more accurate than b-ultrasound in evaluating vaginal fornix and uterine infiltration ( p < 0.05) [ 46 ]. Furthermore, SWE was evaluated for uterine and vaginal fornix invasion, and the results showed that SWE was more accurate in assessing vaginal fornix and uterine invasion than B-mode sonography only ( p < 0.05) [ 48 ].…”
Section: Cervical Tumorsmentioning
confidence: 99%